Scattered Particles Removal in Single Image for Technology of Hologram - Lazim Talib, Muhamad; Abdul Wahab, Norshahriah; Faidzul Nasruddin, Mohamad; Norul Huda Sheikh Abdullah, Siti (International Journal of Engineering and Technology, 2018)
Scene image captured by vision devices usually occluded by scattered atmospheric particles. The quality of image usually corrupted by this problem. Recent researches usually do the image enhancement and recovery method to solve the problem. Doing image enhancement usually eliminate some potential scene information accidently. Previous researchers did the recovery methods to remain the potential information physically. They did veil estimation, depth transmission estimation and reflectance layer estimation to remove the scattered particles. By doing this, image may contain unreliable value added in veil estimation and transmission. So that the scene of image structure was disturbed. This research did the potential illumination estimation that influence the scattered particles occurred in the image. Result of the experiment proved that this method to reliable value to remove in the image was remained by Structure Similarity Index Matrix(SSIM).Â Â